Synthesis of fine particles of ZnO at 100 degrees C - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of fine ZnO at 80-100 degreesC under refluxing conditions. Freshly prepared zinc hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 4-6 It. Formation of fine crystallites of ZnO is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for these powders. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction